PENGARUH KEPEMIMPINAN, MOTIVASI DAN KEDISIPLINAN TERHADAP KINERJA KARYAWAN PADA PT. SANTIKA PREMIERE DYANDRA HOTEL DAN CONVENTION MEDAN - Asima Rosiana Purba; Novi Yuliani Hutagalung; Erlena Putri; Hendra Nazmi (Jurnal Ilmu Manajemen METHONOMIX, 2020)
The study was conducted to determine the effect of leadership, motivation, and discipline on employee performance at PT. Santika Premiere Dyandra Hotel and Medan Convention. The population is 202 employees. The number of samples in this study was 134 employees and the validity and reliability testing was 30 employees. The sampling technique used is simple random sampling. The results showed that simultaneously leadership, motivation, and discipline had a positive and significant effect on employee performance at PT. Santika Premiere Dyandra Hotel and Medan Convention. Partially, leadership, motivation and discipline had a positive and significant impact on employee performance at PT. Santika Premiere Dyandra Hotel and Medan Convention.